2016
DOI: 10.3733/ca.v070n01p15
|View full text |Cite
|
Sign up to set email alerts
|

Biological control program is being developed for brown marmorated stink bug

Abstract: B rown marmorated stink bug (BMSB), Halyomorpha halys (Stål) (Hemiptera: Pentatomidae), has a native range that includes China, Japan, Korea and Taiwan. Its host plant range extends to more than 170 species, among which are valuable ornamentals and agricultural fruit, nut and vegetable crops (Lee et al. 2013;Rice et al. 2014). BMSB can cause direct injury to crops while using its piercing-sucking mouthparts to feed. Characterization of feeding injury to marketable crops such as surface discoloration, depressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…Researchers at the USDA ARS Beneficial Insect Introduction Research laboratory were in the process of evaluating T. japonicus for potential release as a classical biological control agent when it was first discovered that the species had arrived in North America in Beltsville, MD in 2014 as an accidental introduction (Talamas et al, 2015) and was subsequently discovered in Washington state in 2015 (Milnes et al 2016). Researchers at the University of California Riverside are also investigated the potential of using T. japonicus as a classical biological control agent against BMSB in California (Lara et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers at the USDA ARS Beneficial Insect Introduction Research laboratory were in the process of evaluating T. japonicus for potential release as a classical biological control agent when it was first discovered that the species had arrived in North America in Beltsville, MD in 2014 as an accidental introduction (Talamas et al, 2015) and was subsequently discovered in Washington state in 2015 (Milnes et al 2016). Researchers at the University of California Riverside are also investigated the potential of using T. japonicus as a classical biological control agent against BMSB in California (Lara et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Both nymphs and adults capture prey of different sizes, and feed individually or in aggregations. Since the discovery of the brown marmorated stink bug in Pennsylvania in 1996 (Hoebeke & Carter 2003), attempts have been made to use parasitoids and predators (Dieckhoff & Hoelmer 2014;Lara et al 2016) as a sustainable management option of this new invasive polyphagous Asian immigrant (Hamilton et al 2008;Haye et al 2015;Leskey & Nielsen 2018) that has been reported in 44 states, including a limited reproductive localized infestation in Lake County, Florida (Northeastern IPM Center 2017; Penca & Hodges 2018). In this laboratory study, we determined the feeding response of E. floridanus to brown marmorated stinkbug Halyomorpha halys (Stål) (Hemiptera: Pentatomidae) nymphs and adults in controlled environmental conditions.…”
Section: Feeding Responses Of Euthyrhinchus Floridanus (Hemiptera: Pementioning
confidence: 99%
“…In 2014, an Asian egg parasitoid, Trissolcus japonicus (Ashmead) (Hymenoptera: Scelionidae), was found successfully parasitizing laboratory reared, field deployed (sentinel) H. halys egg masses in Beltsville, Maryland, USA (Talamas et al 2015;Herlihy et al 2016). Several other field populations have since been reported in the mid-Atlantic and Pacific Northwestern regions of the US (10 states and Washington, DC, Hoelmer personal communication), which likely represent multiple independent introductions of the parasitoid (Milnes et al 2016;Lara et al 2016;Hedstrom et al 2017). It is unclear through what pathways T. japonicus entered North America, but genetic data indicate that the parasitoid did not escape from quarantine facilities where it is being studied as a potential classical biological control agent of H. halys (Bon et al 2017).…”
Section: First Report Of Trissolcus Japonicus Parasitizing Halyomorphmentioning
confidence: 99%
“…To our knowledge, these are the first observations of successful parasitism of H. halys by T. japonicus on a cultivated crop in the US that occurred in 2 different orchards. In China, the percentage of each H. halys egg mass attacked by T. japonicus ranges between 20% and 80% of eggs, with a season-long average parasitism of each egg mass of 50% among field collected egg masses on fruit and forest trees (Yang et al 2009;Lara et al 2016). In northern China, T. japonicus was the dominant egg parasitoid attacking H. halys sentinel egg masses deployed in cultivated peach, mulberry (Morus alba L.; Moraceae), and jujube (Ziziphus jujuba Mill.…”
Section: First Report Of Trissolcus Japonicus Parasitizing Halyomorphmentioning
confidence: 99%